An Institutional Configurational Approach to Cross‐National Diversity in Corporate Governance - Haxhi, Ilir; Aguilera, Ruth V. (Journal of Management Studies, 2017)
AbstractCorporate governance (CG) research has typically been studied from rather disparate disciplinary approaches, thereby offering myopic and often conflicting rationales. We develop an institutional configurational approach to integrate this ‘siloed’ field and explain CG patterns around the world. To do so, we draw on an inductive, theory‐building methodology based on fuzzy‐set logic to uncover the configurations across institutional actor‐centred domains and their impact on CG patterns. Empirically, we explore the necessary and sufficient causal conditions leading to different features of codes of good governance across 32 OECD countries. We generate propositions linking configurational institutional domains to code features. Our results show that a single institutional domain by itself is not sufficient to explain CG outcomes, and that these domains need to be considered in conjunction, leading, in turn, to the identification of four distinct configurational governance prototypes. Our study offers a comprehensive account of drivers of cross‐national differences in CG and yields useful insights for managing and regulating governance.